THE DEDUCTIBILITY OF CONTRIBUTIONS AS BUSINESS EXPENSES. - Filbey, Edward J. (The Accounting Review, 1931)
Abstract The various revenue acts of the United States have neither included nor excluded charitable and similar contributions by corporations as deductible items. The Commissioner and the courts have ruled that they are not deductible. But the laws have made the ordinary and necessary of conducting a business, deductible, and among these expenses the Commissioner, the courts, and the Board of Tax Appeals have included certain contributions by corporations that appeared to have been made with the expectation that direct and immediate benefits would accrue to the corporations as a result of the contributions. Contributions are made by business men either from motives of philanthropy or because they believe that certain benefits will accrue there from to their business. In the case of the individual contributor, both types of contributions should be allowed as deductions. In the case of the corporation, the second type should properly be allowed in practically all cases, in as much as the judgment of the corporation's officials as to the benefits likely to be secured is presumed to be as reliable as that of the Commissioner or his agents.